Modulatory effect of curcumin on survival of irradiated human intestinal microvascular endothelial cells: role of Akt/mTOR and NF-κB - Rafiee, Parvaneh (American Physiological Society, 2010)
Radiation therapy is an essential modality in the treatment of colorectal cancers. Radiation exerts an antiangiogenic effect on tumors, inhibiting endothelial proliferation and survival in the tumor microvasculature. However, damage from low levels of irradiation can induce a paradoxical effect, stimulating survival in endothelial cells. We used human intestinal microvascular endothelial cells (HIMEC) to define effects of radiation on these gut-specific endothelial cells. Low-level irradiation (1–5 Gy) activates NF-κB and the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, which is involved in cell cycle reentry and cell survival in HIMEC. A downstream target of PI3K/Akt is mammalian target of rapamycin (mTOR), which contributes to endothelial proliferation and angiogenesis. The aim of this study was to investigate the signaling molecules involved in the radiosensitizing effects of curcumin on HIMEC subjected to low levels of irradiation. We have demonstrated that exposure of HIMEC to low levels of irradiation induced Akt and mTOR phosphorylation, which was attenuated by curcumin, rapamycin, LY294002, and mTOR small interference RNA (siRNA). Activation of NF-κB by low levels of irradiation was inhibited by curcumin, SN-50, and mTOR siRNA. Curcumin also induced apoptosis by induction of caspase-3 cleavage in irradiated HIMEC. In conclusion, curcumin significantly inhibited NF-κB and attenuated the effect of irradiation-induced prosurvival signaling through the PI3K/Akt/mTOR and NF-κB pathways in these gut-specific endothelial cells. Curcumin may be a potential radiosensitizing agent for enhanced antiangiogenic effect in colorectal cancer radiation therapy.